2009
DOI: 10.1177/0095798409353760
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Early Relationships for African American Children’s Academic and Social Development: An Examination From Kindergarten to Fifth Grade

Abstract: This study investigates the extent to which the quality of the relationships between African American children and their mothers and teachers in kindergarten predict academic and social development during elementary school years using the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development. The role of prior center care and the ethnicity of the kindergarten teacher were also examined as moderators. Hierarchical linear modeling indicated that a close relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…For instance, father is the symbol of power and authority in family and children expect this power to accompany and support them (Kıldan, 2012). Besides, a sustainable and positive father-child relationship develops children's emotional efficiency, social relations, and problem-solving skills (Iruka, Burchinal and Cai, 2010;West, Mathewes and Kerns, 2013). According to Güngörmüş Özkardeş (2015), young children who perceive their fathers as warmer, more affectionate, and friendly share their stuff with their friends more easily and display less aggressive behaviours.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…For instance, father is the symbol of power and authority in family and children expect this power to accompany and support them (Kıldan, 2012). Besides, a sustainable and positive father-child relationship develops children's emotional efficiency, social relations, and problem-solving skills (Iruka, Burchinal and Cai, 2010;West, Mathewes and Kerns, 2013). According to Güngörmüş Özkardeş (2015), young children who perceive their fathers as warmer, more affectionate, and friendly share their stuff with their friends more easily and display less aggressive behaviours.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Iruka, Burchinal and Cai (2010) investigated the long term effects of relationships in kindergarten with teachers and found a positive correlation between supportive and caring teacher-child relationships and successful navigation of the education system up to fifth grade. Crucially they found that positive relationships between teachers and their pupils enabled appropriate social behaviour within school, and from a communities of practice perspective, engaging in the valued practices of a community is essential for learning.…”
Section: Relationships In Educationmentioning
confidence: 99%
“…The literature discussed previously (Iruka et al, 2010;Raskauskas et al, 2010;Lizzio et al, 2011) demonstrates that positive interpersonal relationships decreased discipline problems in school and increased appropriate social behaviours. The student participants in this study accepted the need for some rules, and judged teachers who failed to maintain the rules of order in classrooms harshly:…”
Section: Rules and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…We define parent sensitivity during the early school years as mothers' supportive, positive, and non‐intrusive behavior during interaction with the child. Previous research on these constructs using the SECCYD dataset at the early school‐aged assessments has demonstrated significant associations between both maternal sensitivity and mother–child conflict with mother and teacher reports of children's social competence across middle childhood (Fraley, Roisman, & Haltigan, ; Iruka, Burchinal, & Cai, ).…”
Section: Introductionmentioning
confidence: 99%